[Maritime] The impact of port disruptions on supply chains - Lin, Jason Jiesheng. (2011)
With the significant role that ports play in the modern global supply chain as well as the development of ports, it is crucial to understand that any disruptions to ports will cause an impact on the global economic health. This study serves to identity the direct port disruptions and analyse them via a risk matrix model as well as supportive primary interview sources. Upon generating a risk matrix, it is noticed that the major events that are rare in likelihood has an up scaling effect on the risk matrix model that causes the rest of the disruptive events to appear insignificant. Deemed to be a misleading effect, it is probably better to draw out the major events for separate discussion. Natural disasters and strikes are two of the most common causes of port disruptions and it is also an alarming revelation that strikes are on the rise in today’s modern context. A drastic contrast of the East Asian’s relatively conservative culture as to that of the West, it is unexpected but nevertheless explainable. Adding on is the new-age cause of disruption – marine terrorism, which is a rising concern for the world to prepare for in deterrence.